Comprehensive Public Expenditure Review 2013 : Eye on Budget - Spending for Results - Ministry of Devolution and Planning (Government of Kenya, Nairobi, 2014)
This public expenditure review (PER) provides an assessment of the extent to which expenditure addresses national priorities in an effort to strengthen the link between government policies, planning, and budgeting. This report is prepared to provide a critical assessment of public spending, challenges, weaknesses, and successes in the past three years (2009 to 2012). The report subsequently informs current and future expenditure through policies that influence budget decisions. It links public expenditure to performance of key sectors in the economy for the three year period; while giving policy and performance outlook focusing on the implementation of the constitution of Kenya 2010 in general and devolution in particular. This report gives an outline on sector performance of programs and reviews expenditures for the period. It provides recommendations to improve implementation of the budget in terms of efficiency, effectiveness, timeliness, and target for better service delivery. This report accentuates the institutional reforms underpinned in the constitution of Kenya 2010 and explores the opportunities to catalyze Kenya's growth as envisaged in the economic blue print, the Kenya vision 2030. This report is divided into eight chapters as follows: chapter one is macro-fiscal performance and fiscal framework; chapter two is public finance management; chapter three focuses on education; chapter four focuses on health; chapter five deals with agriculture and rural development sector; chapter six focuses on water, sanitation, and irrigation; chapter seven presents infrastructure; and chapter eight focuses on social protection.